Markägarundersökning om plantor och återbeskogning - Olausson, Alexander (SLU/School for Forest Management, 2015)
The purpose of this report is to review how private forest owners think when they choose methods for reforestation and in particular planting and seedlings. Also hopefully start some thoughts at the forest owners on what kind of seedling they are using when they are planting. The method used for the survey was a mail questionnaire sent to 247 forest owners in the parish of Lannaskede outside Vetlanda in Jönköping County, Sweden. All of the forest owners had a forest area larger than 35 hectare. Out of the 247 forest owners 126 answered, which is 51 percent of the total. One thing that probably affected the amount of forest owners that answered the questionnaire is that the address register used was nearly two years old. A lot can happen on that time, people can sell their estate or they can die.